Economics, Ergonomics, Effectiveness: A Monocentric Comparison of Single-Use vs. Reusable Flexible Ureteroscopes in Challenging Kidney Stone Cases - Ozimek, Tomasz; Günzel, Karsten; Galuszka-Ozimek, Natasza; Wießmeyer, Judith Riccarda; Becker, Benedikt; Busch, Jonas Felix; Hinz, Stefan; Magheli, Ahmed; Kramer, Mario; Merseburger, Axel S.; Roesch, Marie Christine (Aktuelle Urologie, 2025)
Hybrid strategies involving the use of both single-use flexible ureteroscopes (sufURS) and reusable flexible ureteroscopes (rfURS) are being implemented worldwide to extend the longevity of rfURS. We present a retrospective comparison of the clinical performance, ergonomics, and financial aspects between sufURS and rfURS.Challenging cases were preoperatively selected based on the presence of nephrolithiasis requiring laser lithotripsy and a steep preoperative infundibulopelvic angle (IPA) < 50°. All procedures were performed at the UKSH Campus Lübeck between January 2020 and March 2021 using sufURS (Pusen PU3022A) and rfURS (Olympus URF-V3). Postoperative surveys to evaluate the performance and ergonomics were completed by the surgeon and the assisting nurse.A total of 29 sufURS procedures were followed by 25 rfURS procedures. Stone characteristics in both groups were comparable (p > 0.05). No statistically significant differences in clinical outcomes were observed, including stone-free rate, median operation time, or the rate of Clavien-Dindo ≥ 2 complications (p > 0.05). Surgeons found sufURS to be significantly better suited for accessing the lower calyx. Assisting nurses rated sufURS as significantly easier to assemble and dismantle. The overall cost per case was comparable between sufURS (€749) and rfURS (€791).Both sufURS and rfURS perform comparably for challenging nephrolithiasis cases. sufURS does not offer a clear financial advantage over traditional rfURS.
Keywords: single-use; ergonomics; cost analysis; flexible ureteroscopy; reusable